Pure Gospel or Full Gospel: On the Principles of Lutheran and Pentecostal Theology. Issue 4 (December 2016) - Vondey, Wolfgang
Abstract: The claim in recent conversations among Lutherans and Pentecostals that the "pure gospel" and "full gospel" paradigms held respectively by each tradition represent contrasting theological principles is examined through a historical and theological study of the notion of "gospel." The two paradigms, although not mutually exclusive, identify different hermeneutical and doctrinal commitments that suggest that the contrast between the two traditions exists not in the idea of the gospel but in its mode of expression.